2009
DOI: 10.1002/bdd.678
|View full text |Cite
|
Sign up to set email alerts
|

High dose methotrexate population pharmacokinetics and Bayesian estimation in patients with lymphoid malignancy

Abstract: The purpose of present study was to develop a population pharmacokinetic model of high dose methotrexate (HD-MTX) infusion in patients with lymphoid malignancy, to investigate the biological and clinical covariates related to the drug distribution and elimination. It is also the purpose to propose a limited sampling strategy (LSS) for the estimation of the time above the threshold (0.2 micromol.L(-1)). A total 82 patients with lymphoid malignancy were involved in the study. A pharmacokinetic model was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 26 publications
10
34
2
Order By: Relevance
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This pair of parameters had been included in most of the previously reported population parameters. 9,[11][12][13][14][15][16][17][18][19] This result indicates that the reported population parameters may be inappropriate for the Bayesian least-squares method used in the present study. Thus, we compared correlations among the possible combinations of population parameters.…”
Section: Discussionmentioning
confidence: 84%
“…The former was the combination that had the weakest correlations in the present study, and the latter was the most frequently reported combination in previous studies. [9][10][11][12][13][14][15][16][17][18][19] As shown above, the sum of the absolute value of correlation coefficients among V 1 , k 10 , k 12 , and k 21 was 1.05 for regimen B, whereas V 1 , V 2 , CL, and Q was 3.29 for regimen B. Because of the relatively strong correlations among V 1 , V 2 , CL, and Q, this combination of the population parameters was considered to be a good target for a comparison with V 1 , k 10 , k 12 , and k 21 .…”
Section: Evaluation Of the Effect Of Correlations Among Population Pamentioning
confidence: 99%
See 2 more Smart Citations
“…A number of population-based pharmacokinetic models of HDMTX infusion in patients with lymphoblastic malignancies have been described [10][11][12]. However, the clinical application of these models, particularly for patients with delayed elimination of MTX, is limited because of the considerable variation between patients in terms of MTX dosage, hydration and alkalization, renal function, coadministration of other anticancer agents, and pharmacogenomics [2,7,13].…”
mentioning
confidence: 99%